2014
DOI: 10.18632/oncotarget.2608
|View full text |Cite
|
Sign up to set email alerts
|

EBV-driven LMP1 and IFN-γ up-regulate PD-L1 in nasopharyngeal carcinoma: Implications for oncotargeted therapy

Abstract: PD-L1 expression is a feature of Epstein-Barr virus (EBV) associated malignancies such as nasopharyngeal carcinoma (NPC). Here, we found that EBV-induced latent membrane protein 1 (LMP1) and IFN-γ pathways cooperate to regulate programmed cell death protein 1 ligand (PD-L1). Expression of PD-L1 was higher in EBV positive NPC cell lines compared with EBV negative cell lines. PD-L1 expression could be increased by exogenous and endogenous induction of LMP1 induced PD-L1. In agreement, expression of PD-L1 was sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
332
4
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 345 publications
(355 citation statements)
references
References 51 publications
17
332
4
2
Order By: Relevance
“…The in vitro findings suggest that EBV infection may happen first in the pathogenesis of NPC and MSI can be induced by EBV. In addition, our results confirm findings of other studies [14][15][16][17] that positive PD-L1 expression is frequent in NPCs, but is not associated with clinicopathologic parameters. Although it was previously reported as an independent predictor of survival [16], in our cohort from the Philippines, positive PD-L1 expression was not associated with OS.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The in vitro findings suggest that EBV infection may happen first in the pathogenesis of NPC and MSI can be induced by EBV. In addition, our results confirm findings of other studies [14][15][16][17] that positive PD-L1 expression is frequent in NPCs, but is not associated with clinicopathologic parameters. Although it was previously reported as an independent predictor of survival [16], in our cohort from the Philippines, positive PD-L1 expression was not associated with OS.…”
Section: Discussionsupporting
confidence: 91%
“…PD-L1 expression was described in other EBV-associated malignancies [11][12][13] and several studies have reported positive PD-L1 expression in 25-89% of NPCs [14][15][16][17]. In contrast to EBV-associated gastric adenocarcinomas in which expression of PD-L1 protein may result from PD-L1 gene amplification [18], NPCs do not have PD-L1 gene copy number change [19].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations